Analysis of Steaming Ecoprint Techniques on Various Fabrics - Purwosiwi Pandansari; Rina Purwanti; Dessy Ayu Alfianti (Formosa Journal of Social Sciences (FJSS), 2022)
Experimental analysis research is an effort to test textile materials that are suitable for making textile motifs with the stem eco print technique in order to find good quality textile materials. The development of fashion has had a major impact on one's creativity in processing and developing its products. The ecoprint technique is an option in making product variations. Textile materials suitable for stem techniques and raw materials to produce unique fabric motifs. This type of research is descriptive qualitative to observe the color results of the same type of leaves on different types of fabrics. The eco print results from three fabric materials, namely, ero, mori, and cotton, there are significant differences, the influence of the raw material for leaves as the media looks the best for ecoprint media, there are 2, namely cotton. Mori Cotton and Japanese Cotton for clothing materials. While the calico cloth is for household linen